Sprinting performance of individuals with unilateral transfemoral amputation: compensation strategies for lower limb coordination. Issue 3 (8th March 2023) - Hu, Mingyu; Kobayashi, Toshiki; Hisano, Genki; Murata, Hiroto; Ichimura, Daisuke; Hobara, Hiroaki
Abstract : Understanding the sprinting patterns of individuals with unilateral transfemoral amputation (uTFA) is important for designing improved running-specific prostheses and for prosthetic gait rehabilitation. Continuous relative phase (CRP) analysis acquires clues from movement kinematics and obtains insights into the sprinting coordination of individuals with uTFA. Seven individuals with uTFA sprinted on a 40 m runway. The spatio-temporal parameters, joint and segment angles of the lower limbs were obtained, and CRP analysis was performed on thigh-shank and shank-foot couplings. Subsequently, the asymmetry ratios of the parameters were calculated. Statistical analyses were performed between the lower limbs. Significant differences in the stance time, stance phase percentage, ankle joint angles and CRP of the shank-foot coupling ( p < 0.05) were observed between the lower limbs. The primary contributor to these differences could be the structural differences between the lower limbs. Despite the presence of different coordination features in the stance and swing phases between the lower limbs, no significant difference in the coordination patterns of the thigh-shank coupling was observed. This may be a compensation strategy for achieving coordination patterns with improved symmetry between the lower limbs. The results of this study provide novel insights into the sprinting movement patterns of individuals with uTFA.